The role of lncRNAs in the tumor microenvironment and immunotherapy of melanoma - Zhou, Wencheng; Xu, Xuewen; Cen, Ying; Chen, Junjie (Frontiers in Immunology, 2022)
Melanoma is one of the most lethal tumors with highly aggressive and metastatic properties. Although immunotherapy and targeted therapy have certain therapeutic effects in melanoma, a significant proportion of patients still have drug resistance after treatment. Recent studies have shown that long noncoding RNAs (lncRNAs) are widely recognized as regulatory factors in cancer. They can regulate numerous cellular processes, including cell proliferation, metastasis, epithelial-mesenchymal transition (EMT) progression and the immune microenvironment. The role of lncRNAs in malignant tumors has received much attention, whereas the relationship between lncRNAs and melanoma requires further investigation. Our review summarizes tumor suppressive and oncogenic lncRNAs closely related to the occurrence and development of melanoma. We summarize the role of lncRNAs in the immune microenvironment, immunotherapy and targeted therapy to provide new targets and therapeutic methods for clinical treatment.